Past Migrations and Their Consequences from a Lifelong Perspective: Reflections of Polish 1980s Migrants - Dziekońska, Małgorzata (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2022)
In today’s dynamic world, migration is gaining more scope; it is more complex and analysed from many perspectives. One of those is provided by past migrations. In 2020, a study concerning Polish residents who migrated internationally in the 1980s was performed. Its results not only offer another perspective on the past migration experience but, above all, on its lifelong consequences. The financial needs satisfied at that time resulted in considerable improvement of migrants’ family’s living conditions and, in many cases, also contributed to better family’s financial standing later in life. However, in the whole life view, regardless of the financial assets gained, the migration, which was a threat to the family’s stability in many respects, was assessed as a mistake of the lifetime.